2023
DOI: 10.3390/plants12051192
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Invasiveness, Thermotolerance and Light Requirement of Nine Invasive Species in China

Abstract: Understanding responsible functional traits for promoting plant invasiveness could be important to aid in the development of adequate management strategies for invasive species. Seed traits play an important role in the plant life cycle by affecting dispersal ability, formation of the soil seed bank, type and level of dormancy, germination, survival and/or competitive ability. We assessed seed traits and germination strategies of nine invasive species under five temperature regimes and light/dark treatments. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 90 publications
(97 reference statements)
1
6
0
Order By: Relevance
“…In the case of R. obtusifolius, Figure 2 clearly shows its antagonistic effect. When it comes to PC2, the most important factors favoring the germination of R. obtusifolius are SYN, SH and SW. SH and SW clearly show us that slightly heavier seeds have a favored faster germination, while lighter seeds may present slower germination, a fact that was recently demonstrated in a study with nine other invasive species from China [58]. Arthrocnemum macrostachyum and Suaeda vermiculata, other invasive species from China, showed the same behavior [34] as well as 19 other species studied [59] in the same climate and natural conditions as those presented in this work.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In the case of R. obtusifolius, Figure 2 clearly shows its antagonistic effect. When it comes to PC2, the most important factors favoring the germination of R. obtusifolius are SYN, SH and SW. SH and SW clearly show us that slightly heavier seeds have a favored faster germination, while lighter seeds may present slower germination, a fact that was recently demonstrated in a study with nine other invasive species from China [58]. Arthrocnemum macrostachyum and Suaeda vermiculata, other invasive species from China, showed the same behavior [34] as well as 19 other species studied [59] in the same climate and natural conditions as those presented in this work.…”
Section: Discussionsupporting
confidence: 84%
“…Lara, et al [60], studying the effect of the source of nitrate used on the germination of Lycopersicon esculentum, also showed a higher MGT with lower SYN values. Eight different pasture-forming grasses also showed the same antagonistic behavior between SYN and TMG [58]. In this same PCA, we can infer that larger seeds have a lower germination with a lower synchrony.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This increase in leaf temperature is inversely related to photosynthesis, often leading to reduced photosynthetic activity, as shown in this study, where these features showed a negative correlation (r = −0.692) between them. On the other hand, plants inhabiting arid and xerophytic habitats tend to exhibit characteristics that promote the formation of smaller, thicker leaves [22,36,40,86,87]. Larger leaves tend to possess reduced convection coefficients and exhibit greater resistance to heat transfer through the boundary layers of the leaves in comparison to their smaller counterparts [69].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, narrow germination requirements may promote invasion success by ensuring favorable conditions for seedling establishment, such as through microhabitat selection (Carvalho et al 2021; Gioria et al 2018; Kudoh et al 2007; Makana and Thomas 2005; Marushia et al 2010; Stromberg et al 2007; Wainwright et al 2012). As plants may encounter diverse environmental conditions following initial dispersal to new locations, broad light requirements for germination may strongly influence where invasive plants may be successful, whereas strict light requirements may optimize seedling establishment and growth (Bhatt et al 2023; Castillo et al 2013).…”
Section: Introductionmentioning
confidence: 99%